Analysis of means of personal protection for rescuers during incidents involving radioactive materials - Bozena Kukfisz; Marzena Polka (Scientific Journal of the Military University of Land Forces, 2018)
During firefighting and rescue operations there is a high probability that rescuers will come into contact with ionizing radiation and radiation contamination. The firemen of the State Fire Service and the Volunteer Fire Service perform a number of tasks during the action [Obwieszczenie Marszałka Sejmu… 2009], for which they are prepared during exercises and theoretical sessions. A significant reduction in the probability of radiation or radiation contamination risk can be achieved by taking appropriate precautions and following certain rules and procedures. The actions at which ionizing radiation occurs take place very rarely and procedures are regulated by the “Rules of conduct in the event of radiation risk” [Komenda Główna… 2009] annexed to the “Rules of the organization of chemical and environmental rescue in the National Firefighting and Rescue System” [Komenda Główna… 2013]. The aim of this article is to present the possibilities of protecting the rescue team during fire and rescue operations associated with the potential presence of radioactive materials at the scene.